Tet3-mediated DNA demethylation is essential for maintaining the dedifferentiation capacity of mammalian Müller glia - Martinez-Colin, Erick J.; Lezama, Ivonne; Ochoa-de la Paz, Lenin D.; Lamas, Monica (Frontiers in Molecular Neuroscience, 2025)
Müller glia (MG) are retinal resident cells with diverse functions, including reprograming and regeneration in certain species. While the mammalian retina possesses molecular mechanisms for MG dedifferentiation and neuronal differentiation, it fails to generate neural progenitors in vivo. We previously proposed that an epigenetic barrier, driven by DNA methylation, may prevent complete MG reprograming in response to damage. DNA demethylases, such as Ten-Eleven Translocation (TET) and Growth Arrest and DNA Damage-Inducible Protein 45 (GADD45) families, are induced by damage and play roles in cellular reprograming and regeneration. Tet enzymes are regulated by metabolic factors (iron, vitamins A and C) and respond to environmental stimuli. Here, we investigated DNA demethylation as a regulatory signal for MG dedifferentiation and neuronal differentiation in response to N-methyl-D-aspartate (NMDA), a neurotransmitter used to model retinal neurodegeneration. Using mouse primary cultures and antibodies against methylated (5mC, MeCP2) and unmethylated (5 hmC, H3K4Me3) DNA, we analyzed MG epigenetic changes under control, vitamin-supplemented, and NMDA-stimulated conditions. We also assessed DNA demethylase expression and key reprograming genes (Ascl1, Lin28, Nestin). Vitamin A and C increased 5hmC levels but did not upregulate Tet enzymes or reprograming genes. In contrast, NMDA increased Tet3 and reprograming gene expression. Tet3 knockdown led to a rapid 5mC increase and impaired NMDA-induced upregulation of Ascl1, Lin28, and Nestin, suggesting its critical role in MG dedifferentiation. Conversely, Tet3 overexpression induced morphological changes and early neuronal marker expression. These findings identify Tet3 as a key epigenetic regulator of MG reprograming and a potential target for retinal regeneration strategies.